(untitled) (Journal of Public and Nonprofit Affairs, 2022)
The COVID-19 pandemic massively affected the nonprofit sector. This article explores how the crisis has impacted nonprofit organizations at a U.S.–Mexico border community with a large population of minorities and migrants. Guided by resource dependency theory and the nonprofit capacity building framework, surveys reveal that nonprofits with less financial support from the government sector, low leadership, and weak operational capacities receive critical impacts from the pandemic. The findings also show that local nonprofits are bonded closely to the community during the pandemic, which reflects the collectivistic culture in Hispanic/Latino communities. This study provides important insights on how local nonprofits with limited resources and an increase in demand from vulnerable populations struggled with the pandemic.